Designing Asynchronous Online Discussion Forum Interface and Interaction Based on the Community of Inquiry Framework - Hasani, Lintang Matahari; Santoso, Harry Budi; Junus, Kasiyah (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
The community of inquiry (CoI) framework describes a process for creating collaborative learning through three elements or presences: social, cognitive, and teaching. Despite its popularity among researchers and practitioners, use of the CoI model is limited to mapping instructional activities, which are yet to be developed into an interaction design for online collaborative learning intended to support the CoI presences. This study was aimed at developing the interaction design of an asynchronous online discussion forum employing a user-centered design method contextualized to the learning-centered design approach. Seven scenario and user interfaces were created to facilitate one introductory activity and four phases of inquiry. The design was evaluated through contextual interviews with ten students. The interviews revealed that the prototype encouraged and supported (a) introductory activity (social presence), (b) idea exploration (cognitive presence), (c) summarizing the discussion (cognitive presence), and (d) facilitating discussion (teaching presence). Future research could be aimed at improving the proposed design based on recommendations and developing a fully functional working system to be tested in real settings.